Deposition and Dissolution of Cr-P Alloy: A Cyclic Voltammetric Approach - C. N. Tharamani, V. S. Murulidharan, and S. M. Mayanna (International Journal of Electrochemical Science, 2007)
Cyclic voltammetric experiments were carried out on platinum microelectrode in acidic solution (pH 3.0) containing chromium sulphate, potassium thiocyanate and sodium hypophosphite. Spectral U.V. absorption studies indicate the complexation of Cr3+ with potassium thiocyanate. The deposition of Cr involves a stepwise reduction mechanism. The results under transient polarization conditions infer the reduction of Cr2+ ions with second electron transfer as a slow step. The observed cyclic voltammetric data show that the alloy deposition is possibly from Cr-complex. Stripping voltammograms show the existence of chromium rich alloy phases. X-ray diffraction data further confirms the phases to be Cr3P and Cr12P7.